НОВЫЕ ПЕДАГОГИЧЕСКИЕ ТЕХНОЛОГИИ В СОВРЕМЕННОМ УЧЕБНОМ ПРОЦЕССЕ - rulen, kosse (FILOLOGIYA UFQLARI JURNALI, 2021)
Use of pedagogical new technologies in the modern educational process The article deals with the issues of new pedagogical technologies in the modern educational process , which will help students to learn their quality in education, learn the material in the disciplines and in the future become good specialists in their field.